Family Experience in Dealing with Emergency Cardiovascular Disease - Ratna Puji Priyanti; Anja Hesnia Kholis; Asri Asri; Rifa'i Rifa'i; Supriliyah Praningsih (Universitas Airlangga, 2019)
Discusiion: The risk of cardiovascular disease has shifted. Cardiovascular disease initially only affected certain age groups but not with the current incidence of cardiovascular disease. This makes the community more susceptible to cardiovascular disease attacks. An attack of cardiovascular disease, in general, is only considered to be a cursory attack. The patients with high-risk factors must be supported by the ability of families to recognize and perform first aid in cardiovascular disease attacks. The purpose of this study was to understand the family's experience in dealing with emergency heart disease at home.Method: This study used qualitative research with a case study approach; 2 participants with family members who face emergency heart disease were selected. The data collection used semi-structured interview techniques using observation and field notes. The data analysis used Creswell's qualitative data analysis method.Result: The results of the study found 4 themes related to the family experience in dealing with emergency heart disease at home. The themes were knowledge, past experience, values and beliefs.Conclusion: The conclusion of the study is that the family experience when dealing with emergency heart disease is strongly influenced by the knowledge that forms a value and belief which then influences the attitudes involved in decision making.